Inventarisasi spesies ikan bernilai ekonomis di perairan umum Kabupaten Seruyan - Mustaqiim Pangestu; S Siswanto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
The purpose of the study was to inventory of fish economic value species in freshwaters Seruyan Regency. Observations and sampling were conducted at three stations that is, the station I (Seruyan Hilir), station II (Danau Sembuluh and Seruyan Raya), station III (hanau) by observing the catch of local fishermen. The study was conducted through desk study and field survey in Seruyan River, Seruyan District, Central Kalimantan Province. Based on the catch of fishermen, daily collection, the number of fish species found during the research took place from three stations as many as 25 species from 13 families. Bagridae family (one species), Anabantidae (four species), Channidae (three species), Cyprinidae (five species), Eleotridae (one species), Synbranchydae (one species), Siluridae (four species), Osphronemidae (one species), Pangasidae (one species), Botiidae (one species), Family Notopteridae (one species), Pangasidae (one species) and Palaemonoidae (one species). Based on these results the cyprinidae family is the most caught family. Keywords : Inventory, Fish Species, Freshwaters, Seruyan Rivers